Left Atrial Volume and Strain by Two‐Dimensional Versus Three‐Dimensional Echocardiography in Healthy Subjects: Reference Values are Not Interchangeable. - Li, Lei; You, Chunyuan; Yan, Xiaoyang; Jin, Yan (Echocardiography, 2026)
Background: Little is known about the differences in left atrial (LA) volume and strain assessed with two‐dimensional (2DE) and three‐dimensional echocardiography(3DE). Therefore, this study aimed to compare 2DE and 3DE parameters in healthy subjects. Methods: We obtained LA volumes and strains by 3DE and 2DE in 328 healthy subjects (52 ± 13 years; 51.83% men). Results: Means of 3DE LA volume indexes (LAVIs) were higher than those derived from 2DE (maximal LAVI: 26.75 vs. 22.66 mL/m2; minimal LAVI: 11.76 vs. 9.30 mL/m2; preA LAVI: 19.52 vs. 16.23 mL/m2, respectively, all p < 0.001). Conversely, means of 3DE LA phasic strains were lower than those derived from 2DE (LA reservoir strain: 25.16 vs. 32.01%; LA conduit strain: 13.09 vs. 16.52%; LA contractile strain: 12.12 vs. 15.52%, respectively, all p < 0.001). Similarly, total, passive, and active LA emptying fractions (EF) were lower with 3DE than those with 2DE (all p < 0.05). Correlation between 3DE and 2DE was moderate for LAVIs (all r > 0.65, all p < 0.001), with 2DE showing a systematic underestimation (bias: −4.09 mL/m2 for maximal LAVI; −2.46 mL/m2 for minimal LAVI, −3.30 mL/m2 for preA LAVI). For LA strain parameters, only conduit strain showed moderate correlation (r = 0.65, p < 0.001) with an overestimation bias of +3.42%, while reservoir and contractile strains correlated poorly between modalities with wide limits of agreement. LAEFs also demonstrated poor inter‐modality agreement. Conclusions: 2DE yielded lower LAVIs but higher LA strain and EF values compared to 3DE. Although there was a significant correlation between the 2D and 3D parameters, agreement analysis indicated that their normal reference values were not interchangeable.